ONTOLOGY OF CULTURE IN CIVILIZATION CONCEPTS OF WORLD HISTORY - Olena Yatsenko ("Scientific Information Agency "Science-technologies-information" LLC, 2019)
Culture is a potential, intuitive, myth-making essence, immanent unity of many of its various manifestations: from the state system to the realization of daily human activity. Civilization is the process of crystallization of living energy in the form of stable forms, the authenticity of which becomes the field of discussion, search and practical philosophy. At this stage, cultural life loses its integrity and organicness, but becomes eclectic and kaleidoscopic. Unlike O. Spengler, N. Danilevsky considers culture a derivative phenomenon of historical and civilizational formation. In his opinion, culture does not degenerate into civilization, but finds in it its fullest and perfect embodiment. The idea of globalization is originally analyzed by the famous sociologist P. Sorokin. He is the author of the theory of the existence of culture supersystems, one of the most original in the history of cultural studies.